Implementasi Model Quantum Teaching Untuk Meningkatkan Motivasi Berprestasi Siswa - Eriyanti, Mahrita; Suyidno, Suyidno; Suriasa, Suriasa (Universitas Lambung Mangkurat, 2014)
The achievement motivation and encouragement in students to perform activities as well as possible in order to achieve a commendable achievement with honors, but in fact the achievement motivation of students of class VIII-B SMP Negeri 2 Anjir Pasar is still low. The general objective of research is to describe the application of the quantum teaching effectiveness in improving student achievement motivation in teaching materials Sound. Specific objectives that describe feasibility studies lesson plans, student achievement motivation, learning outcomes, and student responses. The research using action research model of Hopkins consisting of 3 cycles include planning, action/observation, and reflection. The technique of data collection in the form of tests, observations, questionnaires, and documentation. Data were analyzed by descriptive qualitative and quantitative. The results showed (1) feasibility RPP cycle I, II, and III in general is very good, (2) student achievement motivation cycle I and II are generally good, very good third cycle, (3) improved student learning outcomes with classical completeness cycle I amounted to 71.43% (not complete), the second cycle of 85.00% (complete), and the third cycle 90.91% (complete), (4) students response to the process of teaching is generally good quantum. The conclusion that the implementation of the quantum model of effective teaching increases student achievement motivation class VIII-B SMP Negeri 2 Anjir Pasar on sound teaching materials.